An Interaction Theory Account of (Mediated) Social Touch - Huisman, Gijs (Frontiers in Psychology, 2022)
Research on mediated social touch (MST) has, either implicitly or explicitly, built on theoretical assumptions regarding social interactions that align with `theory theory' or `simulation theory' of social cognition. However, these approaches struggle to explain MST interactions that occur outside of a laboratory setting. I briefly discuss these approaches and will argue in favor of an alternative, `interaction theory' approach to the study of MST. I make three suggestions for future research to focus on.